The Development of Light and Optics Learning Multimedia Oriented Students Creative Thinking Skill - Pajrina Auliyak; Dwi Wiwik Ernawati; Wilda Syahri (Department of Physics Education, Universitas Mataram, 2022)
- The purpose of this research is to develop learning multimedia on light materials and optical tools oriented to students' creative thinking skills that can be used in the learning process either online or offline. This development research uses the Hanaffin and Peck development model. Data was collected using a questionnaire instrument and pretest-posttest questions on creative thinking to 19 students at MTS Nurul Islam Batang Hari. The results of expert validation show that the learning multimedia developed is very feasible to be used in the learning process at the trial stage. The teacher's response and the student's response to the multimedia being studied are very good to use. The test results show that the multimedia developed is very good and feasible to use. Meanwhile, students' creative thinking skills have increased with an N-Gain value of 0.84 which is in the high category. This means that the effective multimedia developed can improve students' creative thinking skills. Further research is expected to be able to develop this learning multimedia on other materials oriented to creative thinking skills or other 21st century skills.